Blattodea as potential indicators of Peninsula Granite Fynbos restoration following the clear-felling of pine plantations - Dyer, Alexei (Department of Biological Sciences, 2014)
Alien plant invasions pose a major threat to the biodiversity of the Cape Peninsula; currently facilitating the transformation of native vegetation and alien invertebrate invasions. This threat provided a motive for the removal of alien pine plantations from the lower slopes of Table Mountain, with the aim of restoring the currently endangered Peninsula Granite Fynbos vegetation. Despite some indication that native fynbos vegetation is recovering, the recovery of native invertebrate communities and their associated ecosystem function remains uncertain. Epigaeic invertebrates are easily sampled, highly abundant, responding rapidly to changes in habitat condition. This study investigates the potential of Blattodea species to be employed as ecological indicators of Peninsula Granite Fynbos restoration, along a chronosequence of recently-felled pine stands. Within 10 years of clear-felling, Blattodea communities inhabiting recovering fynbos do not appear to be very distinct in terms of species richness or composition from those inhabiting undisturbed Peninsula Granite Fynbos, indicating restoration progress. Despite the presence of endemic species among both habitat types, the abundance of the invasive Portuguese millipede (Ommatoiulus moreletii) at clear-felled sites suggests that the ecological footprint of pine still persists. The influence of pine could be reduced by implementing the follow-up clearance of alien trees and pine debris. Although an ecological indicator species was identified, its robustness needs to be tested under a range of spatial and temporal conditions.